The Effect Of Target Training On Shooting Accuracy In Football Extracurricular At SDN Parakanmuncang II - Fauzi, Adriansyah Rizki; Muhtar, Tatang; Dinangsit, Dinar; Lengkana, Anggi Setia (UNIVERSITAS NEGERI MAKASSAR, 2025)
This aims to determine the effect of target practice on shooting accuracy in extracurricular soccer at SDN Parakanmuncang II. The research method used is Quantitative with the Research Design used, namely One Group Pretest-Posttest Design, one group will be given a Pretest before being given Treatment and Posttest after being given Treatment, the Sample used is Random Sampling. Data was collected using a shooting test into the goal. The results of data analysis show the normality test Pretest sig value 0.189> 0.05 while the Posttest value is 0.441> 0.05, it can be concluded that the Pretest-Posttest data has a normal distribution. The Homogeneity Test shows 0.804> 0.05, so the Pretest and Posttest data are Homogeneous. Hypothesis testing using the Paired Sample t-Test Test with a sig value (2-tailed) shows a result of 0.001 <0.05 which means H study 1 is accepted and H 0 is rejected, it can be concluded that there is an effect of target practice on shooting accuracy (accepted). To find out how much influence target practice has on shooting accuracy, the R Square test is carried out with a value of 0.905 x 100 = 90.5%, this shows that each student has an increase from Pretest to Posttest results, it can be interpreted that target practice can improve student shooting accuracy by 90.5%. The results of the study can be concluded that target practice has a significant on the ability of accuracy effect shooting in at extracurricular soccer SDN Parakanmuncang II.